S-310J-2ゴウキ ニヨル カコク デンシ ノ カンソク a. ニュウシャ リュウシ ト オーロラ ダイ 1カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 1 - 久保, 治也; クボ, ハルヤ; 村田, 節夫; ムラタ, セツオ; 伊藤, 富造; イトウ, トミゾウ; 国分, 征; コクブン, ススム; KUBO, Haruya; MURATA, Setsuo; ITOH, Tomizo; KOKUBUN, Susumu (国立極地研究所, 1979)
P(論文) 1977年2月10日に昭和基地から打ち上げられたS-310JA-2号機に,同軸円筒型エネルギー分析器を搭載して,南極電離層中の電子のエネルギースペクトルを測定した.打ち上げ時には地磁気活動が高く,diffuse auroraが発生していた.4.2 keVエネルギーで約1.8×10^3 electrons/cm^2・sec・str・eVの電子フラックスが,また,740 eVのエネルギーでは,約2.3×10^4 electrons/cm^2・sec・str・eVの電子フラックスが観測された.数100 eV近傍のエネルギーの電子は,ピッチ角依存性が大きく,約1.47×10^<-6>A/m^2の電流密度の電子流が,この数100 eV近傍の電子によって,磁力線に沿って流れている. A cylindrical electrostatic analyzer on board the Japanese Antarctic sounding rocket S-310JA-2 launched on February 10, 1977 at Syowa Station obtained the energy spectra of energetic electrons m the Antarctic polar ionosphere. The geomagnetic activity was high and there was a diffuse aurora at the time of launch. The measured electron flux was about l.8×10^3 electrons/cm^2・sec・str・eV at the energy of 4.2 keV and about 2.3×10^4 electrons/cm^2・sec・str・eV at 740 eV. The electrons whose energy was in the neighborhood of 500 eV had a considerable pitch angle dependence, and the field aligned current density due to these electrons resulted in about 1.47×10^<-6> A/m^2. departmental bulletin paper